(Ne)vidnost pokritih žensk - Zalta, Anja (Javnost (Ljubljana), 2018)
The institution of head-covering also in Slovene society is largely understood as one-dimensional and (pre-)general, it is laden with the oriental representation of head-coverage as a sign of subordination and repression, it triggers questions of security and personal freedom, and questions the role of religion in the public sphere and/or secular state. Nevertheless, the main problem does not seem to be the wearing of a headscarf as such, but the question of what the headscarf symbolises. Reckless bans resulting from ignorance of the complexity of the subject, are creating paranoid situations and sowing fear, and are too often justifi ed by the rhetoric of people's protection and welfare. By underwriting such care, intervention agencies such as the media, the state, other leadership and political structures - from religious dignitaries to politicians and state offi cials - legitimise their power and authority, and intervene and dictate the borders of public and private spheres. The purpose of the paper was primarily to explore the motives of head-covering between Slovene Muslim women and Christians (Christian nuns) and to address the reasons for the invisibility of head-covered women in the Slovenian public. The article presents head-covering as a broader problem that addresses the issue of religious presentations and symbolism, cultural discrimination, and also reveals the complexity of (not) hearing women's voices in establishing and preserving their own identity.
Keywords: islam; krščanstvo; muslimanke; pokrivala; redovnice; ženske